BIBLIOMETRIC ANALYSIS OF DEVELOPMENTS AND TRENDS IN FRAUD RISK ASSESSMENT RESEARCH : SCOPUS LITERATURE REVIEW 1989 - 2023 - Rachmat Agus Santoso; Rahmadianti Rahmadianti; Dwi Kartika Sari; Ning Wahyuni (Sean Institute, 2023)
Facing the risk of fraud , organizations need to adopt a proactive and holistic approach to identify, analyze and mitigate potential risks. A common approach is fraud risk assessment , which involves collecting and evaluating data from various aspects of the business, including internal processes, external environment, and human factors that influence the occurrence of fraud . This study aims to analyze in depth the development of the literature regarding fraud risk assessment using the bibliometric method Scopus database . Article selection begins with screening steps to ensure the quality and relevance of the articles in the analysis. This research provides insight into sources, titles, institutions and research trends as well as collaborative network variables in the fraud risk assessment domain . The results of the analysis show fluctuations in the number of publications related to fraud risk assessment over time, with a certain increase in certain years. There are journals which are important sources of this literature, as well as the contributions of authors and institutions in developing an understanding of fraud risk . Provides a broad overview of research developments regarding fraud risk assessment and provides direction trends that the variable task performance of fraud risk assessment can be collaborated on in future research.